Developing an Islamic framework for medical confidentiality practice - Muhsin, Sayyed Mohamed (Faculty of Islamics and Human Sciences, Darul Huda Islamic University, 2021)
Arguably, ethical guidelines and medical laws on medical confidentiality have fallen short of extrapolating the methodology for dealing with potential ethical complexities in its practice. This drawback has made it difficult for physicians to prevent harm from occurring if it has not yet happened, remove harm if it has already taken place, or minimise harm if it is unavoidable. Therefore, this article attempts to outline certain principles in the form of a framework to govern the management of confidential information in light of Islamic legal maxims. This effort is meant to help health workers to deal with conflicting situations, with reasonable care given to those at risk, while maintaining therapeutic trust and professionalism. The notable significance of this framework is that it is structured after identifying the potential harms in the protection and disclosure of medical confidentiality in selected cases from patient's, doctor's and third party's perspectives and addressing each of them with due importance.